The Tormentor from Toruń’s Fort VII, Karl Friedrich Strauss, on the Defendant Bench - Grochowina, Sylwia (Historia i Polityka, 2019)
The paper focuses on the trial of Karl Friedrich Strauss, who from the end of October 1939 until January 1940 served as the administrative commandant of Fort VII in Toruń, which hosted an internment camp for civilians (Zivilinternierungslager). Strauss also participated in executions of Poles in the Barbarka forest near Toruń. The Strauss trial was a trial by jury which took place in June 1969 in the West Berlin district of Moabit. The legal proceedings were widely commented on in the pages of the Pomeranian press, and these press articles serve as the main source material for the present paper. The Strauss trial is one of numerous examples of failure of the denazification process in post-war Germany. Although the crimes committed by the former commander of Toruń’s Fort VII were not in any doubt, the leniency of the German judicial system meant that in the end one of the greatest tormentors of those imprisoned in Fort VII escaped justice and was not punished.